2020
DOI: 10.1093/clinchem/hvaa232
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Blood-Based Detection of Asbestos-Associated Diseases Using Cysteine-Rich Angiogenic Inducer 61 as Circulating Protein Biomarker

Abstract: Background Detection of asbestos-associated diseases like asbestosis or mesothelioma is still challenging. We sought to improve the diagnosis of benign asbestos-associated disease (BAAD) by detection of the protein cysteine-rich angiogenic inducer 61 (Cyr61) in human plasma. Methods Plasma Cyr61 was quantified using an enzyme-linked immunosorbent assay. Plasma samples from males diagnosed with BAAD, but without a malignant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Our present pilot study suggests that circulating CYR61 protein has the potential to serve as a new biomarker for the detection of LC in men. However, this proof‐of‐principle finding needs to be verified in larger study groups of LC patients, including nontumorous lung diseases which could lead to false‐positive signals since it was previously reported that CYR61 is elevated in asbestos‐associated diseases as well [31]. Within the context of LDCT screening, the performance of CYR61 for the use in screening procedures needs to be validated in appropriate prospective studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our present pilot study suggests that circulating CYR61 protein has the potential to serve as a new biomarker for the detection of LC in men. However, this proof‐of‐principle finding needs to be verified in larger study groups of LC patients, including nontumorous lung diseases which could lead to false‐positive signals since it was previously reported that CYR61 is elevated in asbestos‐associated diseases as well [31]. Within the context of LDCT screening, the performance of CYR61 for the use in screening procedures needs to be validated in appropriate prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated CYR61 concentrations have been found in patients with asbestos‐related diseases [ 31 ], and CYR61 is also a tumor‐promoting factor in breast, ovarian, and gastric cancer as well as in gliomas and pancreatic neuroendocrine tumors [ 22 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%